Exploring destination advocacy behavior in a virtual travel community. Issue 5 (13th June 2021) - Lever, Michael W.; Elliot, Statia; Joppe, Marion
ABSTRACT: The use of social media to engage in travel-related discourse plays an increasingly important role in destination choice as users turn to virtual communities where exchanges between visitors and residents thrive. There is growing recognition of the local resident as destination advocate, yet research of online advocacy behavior is limited. This study analyzes 1, 226 messages exchanged among members of a Facebook travel community using netnography, supplemented by several in-depth interviews, to reveal behaviors including sentiment expression, advocate-focused and visitor-focused. The findings extend our understanding of destination advocacy, building on social identity theory to identify unique patterns of co-created social participation.